2016
DOI: 10.1038/srep18944
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian autophagy is essential for hepatic and renal ketogenesis during starvation

Abstract: Autophagy is an intracellular degradation system activated, across species, by starvation. Although accumulating evidence has shown that mammalian autophagy is involved in pathogenesis of several modern diseases, its physiological role to combat starvation has not been fully clarified. In this study, we analysed starvation-induced gluconeogenesis and ketogenesis in mouse strains lacking autophagy in liver, skeletal muscle or kidney. Autophagy-deficiency in any tissue had no effect on gluconeogenesis during sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 31 publications
2
52
0
Order By: Relevance
“…Anaerobic bacterial fermentation of complex polysaccharides yields butyrate, which is absorbed by colonocytes in mammalians for terminal oxidation or ketogenesis (Cherbuy et al, 1995), which may play a role in colonocyte differentiation (Wang et al, 2016). Excluding gut epithelial cells and hepatocytes, HMGCS2 is nearly absent in almost all other mammalian cells, but the prospect of extrahepatic ketogenesis has been raised in tumor cells, astrocytes of the central nervous system, the kidney, pancreatic β cells, retinal pigment epithelium (RPE), and even in skeletal muscle (Adijanto et al, 2014; Avogaro et al, 1992; El Azzouny et al, 2016; Grabacka et al, 2016; Kang et al, 2015; Le Foll et al, 2014; Nonaka et al, 2016; Takagi et al, 2016a; Thevenet et al, 2016; Zhang et al, 2011). Ectopic HMGCS2 has been observed in tissues that lack net ketogenic capacity (Cook et al, 2016; Wentz et al, 2010), and HMGCS2 exhibits prospective ketogenesis-independent ‘moonlighting’ activities, including within the cell nucleus (Chen et al, 2016; Kostiuk et al, 2010; Meertens et al, 1998).…”
Section: Controversies In Extrahepatic Ketogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Anaerobic bacterial fermentation of complex polysaccharides yields butyrate, which is absorbed by colonocytes in mammalians for terminal oxidation or ketogenesis (Cherbuy et al, 1995), which may play a role in colonocyte differentiation (Wang et al, 2016). Excluding gut epithelial cells and hepatocytes, HMGCS2 is nearly absent in almost all other mammalian cells, but the prospect of extrahepatic ketogenesis has been raised in tumor cells, astrocytes of the central nervous system, the kidney, pancreatic β cells, retinal pigment epithelium (RPE), and even in skeletal muscle (Adijanto et al, 2014; Avogaro et al, 1992; El Azzouny et al, 2016; Grabacka et al, 2016; Kang et al, 2015; Le Foll et al, 2014; Nonaka et al, 2016; Takagi et al, 2016a; Thevenet et al, 2016; Zhang et al, 2011). Ectopic HMGCS2 has been observed in tissues that lack net ketogenic capacity (Cook et al, 2016; Wentz et al, 2010), and HMGCS2 exhibits prospective ketogenesis-independent ‘moonlighting’ activities, including within the cell nucleus (Chen et al, 2016; Kostiuk et al, 2010; Meertens et al, 1998).…”
Section: Controversies In Extrahepatic Ketogenesismentioning
confidence: 99%
“…The authors of a classical study concluded that minimal renal ketogenesis quantified in an artificial experimental system was not physiologically relevant (Weidemann and Krebs, 1969). Recently, renal ketogenesis has been inferred in diabetic and autophagy deficient mouse models, but it is more likely that multi-organ shifts in metabolic homeostasis alter integrative ketone metabolism through inputs on multiple organs (Takagi et al, 2016a; Takagi et al, 2016b; Zhang et al, 2011). One recent publication suggested renal ketogenesis as a protective mechanism against ischemia-reperfusion injury in the kidney (Tran et al, 2016).…”
Section: Controversies In Extrahepatic Ketogenesismentioning
confidence: 99%
“…As the liver is a primary tissue controlling both gluconeogenesis and ketogenesis and starvation is a powerful autophagy inducer in the liver and muscle as well, it is plausible to speculate that muscle autophagy could directly impact the liver or vice versa . Although defective autophagy in the muscle causes accumulation of intramyocellular triglycerides and enhanced autophagy facilitates removal of lipids from muscle cells (28), Takagi et al recently demonstrated in tissue-specific ATG5 knockout mice that the mice lacking ATG5 in both the liver and muscle indeed exhibited the improvement of metabolic profile, as compared to liver-specific knockout counterparts, suggesting that autophagy in the skeletal muscle may be metabolically distinct from that in the liver (46). In an independent study, skeletal muscle–specific ATG7 knockout mice also showed lower lipid accumulation and higher expression of β-oxidation–related genes, as compared to control mice (26).…”
Section: Effects Of Muscle Autophagy On the Livermentioning
confidence: 99%
“…Atg7 is also necessary for statin-induced gluconeogenesis in the liver (Wang et al 2015a). Nonetheless, in tissue-specific Atg5–deficient mice, another study suggested that Atg5-related autophagy did not influence gluconeogenesis, but may affect ketogenesis during starvation (Takagi et al 2016). Other than gluconeogenesis, autophagy is also involved in glycogen breakdown in newborn hepatocytes of the rat and skeletal muscles of Drosophila melanogaster (Zirin et al 2013; Kotoulas et al 2006).…”
Section: Autophagy: the Basic Processmentioning
confidence: 99%